A Study on the Important Characteristics associated with the Consumers’ Current Practice of Use of Branded Edible Vegetable Oil (International Journal of Food and Nutritional Sciences, 2023)
Today’s lifestyle has become complex and hypercompetitive. Due to hectic work schedule,priorities and fast-pace life, people hardly care about what they eat, how they eat, whenthey eat. They miss the timelines at times. In addition, getting hygienic food is anotherchallenge. Hence, the manufacturers have come up with edible oils which are more safewith minimum negative impact. They advertise in such manner leading to brands. Thepresent study aims to identify the salient features associated with branded edible vegetableoil. The study is empirical in nature. The statistical tools were applied to collect andanalyze the data. The study is significant as it deals with the health consciousness,marketing strategy and consumer perceptions.